Arginine: What You Need to Know for Pressure Injury Healing. (December 2021) - Chu, Andy S.; Delmore, Barbara
Abstract : GENERAL PURPOSE: To provide information about arginine, its metabolism, and its role in acute and chronic wound healing, to assist providers in understanding the recommendations for arginine supplementation. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Describe the characteristics of arginine. 2. Choose the metabolic processes that define arginine's role in wound healing. 3. Identify the average daily intake of arginine in an American diet. 4. Select the evidence that demonstrates the effectiveness of arginine supplementation for wound healing. ABSTRACT: Nutrition has an important and integral role in wound healing. Arginine, a type of indispensable amino acid, has long been thought to have wound healing properties. The 2019 international guideline by the European Pressure Ulcer Advisory Panel, National Pressure Injury Advisory Panel, and Pan Pacific Pressure Injury Alliance recommends use of a high-protein, high-calorie oral nutrition supplement fortified with arginine and other antioxidants to treat adults with stage 2 or greater pressure injury and who are malnourished or at risk of malnutrition to foster healing. This article provides necessary background on this conditionally indispensable amino acid, its metabolism, and its role in acute and chronic wound healing to assist providers in understanding the recommendation for arginine supplementation.